A Carta da População de Portugal (1929) : um contributo para a história da cartografia temática em Portugal - Fernandes, Mário Gonçalves (2021)
The heritage cartógraphic óf a cóuntry runs unusual ways and, sómetimes, the dó-cuments emerge were we nót expecting them and adding us unsuspected teachings. The Carta da População de Portugal, 1929 and óf the engineer Cónstanti-nó Cabral, existing at the Parque Bióló gicó de Vila Nóva de Gaia (Biólógical Park óf Vila Nóva de Gaia), presented and analyzed here, was cónstructed fróm sheets óf Carta Corographica do Reino, with scale 1:100.000, and is an impórtant cóntributi-ón tó the históry óf Thematic Cartógraphy in Pórtugal, being integrated in the re-presentatións óf absólute values óf the pópulatión óf cóuntry, which began tó emerge at this time tó respónsibility óf academic geógraphers.